The development of the stock market and its effect on economic growth: the case of SADC - Elliott, Kevin Andrew (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
Using a pooled panel data set from nine developing countries within the SADC region from 1992 to 2004, this paper empirically examines; firstly, the relationship between stock market development and long-term economic growth, and secondly, the macroeconomic determinants of stock market development, particularly market capitalisation as a percentage of GDP. The results suggest that there is a strong link between stock market development and economic growth, particularly through the liquidity provided by the market. The evidence obtained lends support to the view that a well-developed and functioning stock market can boost economic growth by enhancing faster capital accumulation and allowing for better resource allocation, particularly in developing countries. In terms of the macroeconomic determinants of stock market development, the results support those of Garcia and Liu (1999), in that we found the indicators of financial intermediary development, the value of shares traded as a percentage of GDP and the macroeconomic instability variable to be important determinants of stock market development.
Keywords: Stocks -- Africa, Southern; Stock exchanges -- Africa, Southern; Economic development -- Africa, Southern; Stocks -- Economic aspects -- Africa, Southern